The right not to know: Some steps towards a compromise - Davies, B; Savulescu, J (Springer, 2020)
There is an ongoing debate in medicine about whether patients have a ‘right not to know’ pertinent medical information, such as diagnoses of life-altering diseases. While this debate has employed various ethical concepts, probably the most widely-used, by both defenders and detractors of the right, is autonomy. Whereas defenders of the right not to know typically employ a ‘liberty’ conception of autonomy, according to which to be autonomous involves doing what one wants to do, opponents of the right not to know often employ a ‘duty’ understanding, viewing autonomy as involving an obligation to be self-governing. The central contribution of this paper is in showing that neither view of autonomy can reasonably be said to support the extreme stances on the right not to know that they are sometimes taken to. That is, neither can a liberty view properly defend a right not to know without limits, nor can a duty view form the basis of an absolute rejection of the right not to know. While there is still theoretical distance between these two approaches, we conclude that the views are considerably closer on this issue than they first appear, opening the way for a possible compromise.